A Community-Based Behavioural Parent Training Model (CiC) to Address ADHD-Related Concerns in the Voluntary Sector in Denmark: A Replication and Extension. Issue 4 (2nd October 2022) - Bangiyev, Violeta; Burger-Calderon, Mirjam; Capó, Zuania; Lui, Nicole; Scavenius, Christoffer; Chacko, Anil
Abstract: Despite demonstrated effectiveness as a psychosocial intervention for youth diagnosed with attention-deficit/hyperactivity disorder (ADHD), behavioural parent training (BPT) remains inaccessible while disorder rates increase globally. Previously, Chacko and Scavenius found that the Caring in Chaos (CiC) BPT model leveraged the advantages of community health settings, resulting in improved child and parent outcomes, prompting a need to replicate these findings. This paper reports on the effects of the CiC BPT model on the previous waitlist, untreated sample from Chacko and Scavenius. Results confirm previous findings, demonstrating CiC BPT improves parenting behaviour, competence, stress, depressive symptoms, and child impairment.